Transformasi Desain Kemasan Produk ChoSik di UPT Sikka Innovation Center Edisi Tahun 2019 dan 2023 - Karrol, Yohanes Paulus; Hidayatullah, Taufan (Universitas Komputer Indonesia, 2025)
ChoSik as the flagship product of Sikka Regency, requires a packaging design that is not only attractive but also reflects the local identity. The packaging design of this chocolate product has undergone four changes since 2018 to date. This research focuses on the design changes between the 2019 and 2023 editions, with the aim to analyze the changes in the form and visual design of Sikka Chocolate product packaging from the 2nd edition 2019 to the 3rd edition 2023, as well as evaluating its impact on the packaging function and representation of local cultural identity in the context of marketing strategy and consumer segmentation. Using an analytical method based on the principles of totality and time according to W. H. Mayall developed by Dr. Ahadiyat Joedawinata, this research evaluates aspects of function (performance), aesthetics (form), and symbolic value (value) in packaging design. Elements such as shape, color, illustration, and typography were analyzed to identify the visual change factors. The results show that there is a significant change in the visual design that leads to modern and minimalist styles, thus reducing the representation of the previously strong local cultural identity. This study provides important insights for designers and the packaging industry in developing products that are in line with local cultural values and market needs. With this approach, design changes not only provide aesthetic benefits but also economic value for regional superior products. Keywords: Sikka Chocolate, Packaging Design, Change, Design